1987
DOI: 10.1007/bf02319466
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic crack curving and branching under biaxial loading

Abstract: A 16 spark-gap camera was used to record the dynamic photoelastic patterns of ten centrally cracked, Homalite-100 specimens which fractured under ten biaxial stress ratios ranging from 3.7 to 0.The dynamic photoelastic patterns of curved cracks were used to verify the previously developed dynamic crack curving criterion. Cracks, which immediately curved upon propagation in three specimens under high biaxial loadings, were used to verify the static counterpart of the dynamic crack curving criterion. A previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 16 publications
(11 reference statements)
1
16
0
Order By: Relevance
“…These studies show that microcracking can explain the increase of fracture toughness with crack velocity and also predict an upper bound for the crack velocity, which lies far below the Rayleigh wave speed. These results agree well with theoretical and experimental findings of other authors (Hawong and Kobayashi, 1987;Ramulu and Kobayashi, 1985;Shukla et al, 1990). Since boundary element methods facilitate the analysis of arbitrary crack paths and the formation of microcracks, crack branching, crack closure and friction, they are being adopted and further developed as an appropriate tool for other macroscopic problems, including problems at the geophysical scale (Fedelinsky and Aliabadi, 1997;Tada and Yamashita, 1997).…”
Section: Fracture Roughness Crack Front Waves and Dissipation Mechasupporting
confidence: 89%
“…These studies show that microcracking can explain the increase of fracture toughness with crack velocity and also predict an upper bound for the crack velocity, which lies far below the Rayleigh wave speed. These results agree well with theoretical and experimental findings of other authors (Hawong and Kobayashi, 1987;Ramulu and Kobayashi, 1985;Shukla et al, 1990). Since boundary element methods facilitate the analysis of arbitrary crack paths and the formation of microcracks, crack branching, crack closure and friction, they are being adopted and further developed as an appropriate tool for other macroscopic problems, including problems at the geophysical scale (Fedelinsky and Aliabadi, 1997;Tada and Yamashita, 1997).…”
Section: Fracture Roughness Crack Front Waves and Dissipation Mechasupporting
confidence: 89%
“…Crack branching in brittle materials has been a subject of theoretical [1][2][3][4] and experimental [5][6][7][8][9][10][11][12][13][14][15][16][17][18] studies. In particular, a criterion which controls the initiation of crack branching has drawn the attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The angle between the branches is determined by the overall state of loading and branches interaction. Hawong et al (1987) performed experiments on homogeneous Homalite-100 and pointed that branching mode and macroscopic branching angle eventually develop strongly depending on the ratio of overall stress applied perpendicular and parallel to the crack. Rafiee et al (2003) confirmed this point through a time-domain boundary element method.…”
Section: Introductionmentioning
confidence: 98%